Communication skills in psychiatry training. (August 2015) - Ditton-Phare, Philippa; Halpin, Sean; Sandhu, Harsimrat; Kelly, Brian; Vamos, Marina; Outram, Sue; Bylund, Carma L; Levin, Tomer; Kissane, David; Cohen, Martin; Loughland, Carmel
Objective: Mental health clinicians can experience problems communicating distressing diagnostic information to patients and their families, especially about severe mental illnesses such as schizophrenia. Evidence suggests that interpersonal communication skills can be effectively taught, as has been demonstrated in the specialty of oncology. However, very little literature exists with respect to interpersonal communication skills training for psychiatry. This paper provides an overview of the communication skills training literature. Conclusions: The report reveals significant gaps exist and highlights the need for advanced communication skills training for mental health clinicians, particularly about communicating a diagnosis and/or prognosis of schizophrenia. A new communication skills training framework for psychiatry is described, based on that used in oncology as a model. This model promotes applied skills and processes that are easily adapted for use in psychiatry, providing an effective platform for the development of similar training programs for psychiatric clinical practice.